(untitled) (Iraqi Journal of Medical Sciences, 2022)
Background: Chronic obstructive pulmonary disease (COPD) is the leading cause of morbidity and mortality worldwide. There is evidence to support a connection between COPD and Diabetes mellitus type 2 (T2DM). T2DM affects 2-37% of COPD patients, with results being highly variable between studies. Objective :To determine the prevalence of T2DM in patients with severe and very severe stages of COPD and to assess the risk factors affecting the prevalence of T2DM among COPD patients. Methods: A cross sectional study was conducted on 140 patients with COPD attending Outpatient and Inpatient of Respiratory Unit at Baghdad Teaching Hospital. The data were collected between the 10th of October 2016 to the 10th of August 2017. These data included demographic parameters such as: age, sex, smoking habit, and respiratory parameters from history and clinical examination. Spirometry was used to assess the severity of COPD patients. Random blood sugar testing was used for identification of COPD patients having T2DM when they are not clear or not known as a case of T2DM previously. Results: The prevalence of T2DM among COPD patients was 19.38%; the prevalence of T2DM in those with severe stage was 10.9%, while in very severe stage was 35.4%. In comparison to women, men were more likely to have T2DM.The prevalence of T2DM increased in the elderly COPD patients (>61 years), with high body mass index, and also increased more among current smokers followed by former smokers and never smokers. Lung function tests decline more in COPD patients with presence of T2DM. Conclusion: T2DM is more common among COPD patients, and its prevalence rose as the severity of the COPD patients’ condition worsened. Additionally, T2DM patients are more likely to experience a decline in pulmonary function. Keywords: Diabetes mellitus type 2, chronic obstructive pulmonary disease, prevalence, random blood sugar Citation: Al-Ani NAH, Al-Obaidy MW. The prevalence of diabetes mellitus type 2 in severe and very severe chronic obstructive pulmonary disease patients. Iraqi JMS. 2022; 20(2): 269-277. doi: 10.22578/IJMS.20.2.15